Genome wide association studies for temperament in New Zealand dairy cattle : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Animal Science in Animal Breeding and Genetics at Massey University, Palmerston North, New Zealand - Chan, Fei Yi (Massey University, 2012)
The aim of this thesis was to identify genomic regions associated with cow temperament in New Zealand dairy cattle. The data set used was provided by the Livestock Improvement Corporation, and contains estimated breeding values (EBV) for temperament of 3140 bulls of three breeds; Holstein-Friesian (HF), Jersey (JE) and Crossbreed (XB) born between 1994 and 2006. Biallelic genotype data were also provided containing 700,000 single nucleotide polymorphism (SNP) markers. Estimated breeding values for cow temperament were adjusted (Adj-EBVtemp) for age, percentage of North American Holstein genes (NAH%), percentage of New Zealand Holstein-Friesian (HF%) and percentage of Jersey (JE%). Using PLINK, the association between individual markers and temperament was investigated. PLINK was also used to produce output with genomic corrected p-values (GC) which adjusts for inflation based on the median chi-square statistic. Suggestive and genome-wide significance thresholds were set at -log10 (1e-4) and -log10 (5e-5) respectively. From literature review, the average estimate of heritability of temperament was 0.17, and average genetic correlation with milk yield was 0.165. JE bulls had the highest average EBV for temperament (0.0352 ± 0.239) followed by XB (0.0079 ± 0.217) and HF bulls (-0.0402 ± 0.256). PLINK analysis show BTA 4 to contain genome-wide significant genomic regions across all three breeds for Adj-EBVtemp. Further investigation on individual chromosomes provided no further information on significant genomic regions affecting temperament. A closer look at many of these regions show they are in domains known as “Junk DNA”. Results suggest that although genomic selection for temperament in dairy cattle is plausible, genetic gain via direct selection for this trait will be slow and desired effects may not be immediate.
Keywords: Dairy cattle; Cows; Genetics; Genome; Breeding; Temperament; Animal behaviour; New Zealand